POTENSI PADATAN TERSUSPENSI (TSS) LIMBAH BUDIDAYA UDANG VANAME (L. vannamei) SISTEM BIOFLOC SEBAGAI SUMBER BAHAN BAKU PAKAN ALTERNATIF - Setiyorini; Ngurah S. Yasa; Joko Purwanto; Wendy Tri Prabowo; A.A.M. Sastrawan Putra (Journal of Fish Nutrition, 2022)
The intensification of vaname shrimp will result in a high load value of suspended solids from shrimp waste. Feed needs have a large percentage in aquaculture activities of 60-70%. The study in this activity aims to see the potential of suspended solids (TSS) as a source of raw materials for alternative feed cultivation. The benefit of this activity is to obtain an alternative source of feed raw materials. The variables used in this activity are suspended solids from vaname shrimp farming waste The way this activity works consists of two stages, namely the collection of suspended solids waste with a waste capture tube (TPL) and testing the nutritional value of suspended solid waste. From the results of the experiment, it can be concluded that suspended solids waste has a protein content of 18-22% and essential amino acids that are quite good and have the potential to be used as alternative feed raw materials for shrimp vanaeme L. vannamei, abalone H. squamata and tilapia O. niloticus.